1997
DOI: 10.1073/pnas.94.3.861
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic H-ras stimulates tumor angiogenesis by two distinct pathways

Abstract: The switch from a quiescent tumor to an invasive tumor is accompanied by the acquisition of angiogenic properties. This phenotypic change likely requires a change in the balance of angiogenic stimulators and angiogenic inhibitors. The nature of the angiogenic switch is not known. Here, we show that introduction of activated H-ras into immortalized endothelial cells is capable of activating the angiogenic switch. Angiogenic switching is accompanied by up-regulation of vascular endothelial growth factor and matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
329
1
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(344 citation statements)
references
References 41 publications
7
329
1
7
Order By: Relevance
“…ROCK1 & 2 are ubiquitously expressed protein kinases. To demonstrate the expression of these paralogs in MILE SVEN 1 (MS1) pancreatic islet endothelial cells, which is a well established mouse endothelial line previously developed in Judah Folkman’s laboratory [24], we performed Western analysis to reveal that both ROCK1 & 2 are present at detectable levels (Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…ROCK1 & 2 are ubiquitously expressed protein kinases. To demonstrate the expression of these paralogs in MILE SVEN 1 (MS1) pancreatic islet endothelial cells, which is a well established mouse endothelial line previously developed in Judah Folkman’s laboratory [24], we performed Western analysis to reveal that both ROCK1 & 2 are present at detectable levels (Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that down regulation of p21-ras causes a decrease of vascular endothelial growth factor (VEGF) production (Arbiser et al, 1997;Okada et al, 1998;Zhang et al, 2001). A bystander effect caused by down regulation of VEGF after p53-gene therapy in vivo has already been described (Bouvet et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…SVR cells, an immortalised murine endothelial cell line over expressing H-ras, form angiosarcoma tumours in vivo [128]. In vitro studies with SVR cells showed that downregulation of MEK (MAPKK), by using clones with dominant negative MEK or by inhibition of MEK with the drug PD98059, resulted in a significant reduction in colony formation [129].…”
Section: Abnormal Growth Signalsmentioning
confidence: 99%
“…pathway in SVR cells did result in significantly smaller angiosarcoma tumours in vivo [128], although independent over expression of Akt1 in murine endothelial cells resulted in benign vascular malformations distinct from angiosarcomas [130]. The viral oncogene v-p3k, of the avian sarcoma virus ASV16, codes for a gene homologous to the catalytic subunit of PI-3-kinase.…”
Section: Abnormal Growth Signalsmentioning
confidence: 99%